T allele of -344C/T polymorphism in aldosterone synthase gene is not associated with resistant hypertension - Lacchini, Riccardo; Sabha, Maricene; Coeli, Fernanda B.; Favero, Fabrício F.; Yugar-Toledo, Juan; Izidoro-Toledo, Tatiane C.; Sandrim, Valéria C.; Tanus-Santos, José E.; de Mello, Maricilda P.; Moreno Jr., Heitor (Springer Nature, 2009)
Resistant hypertension (RH) is the maintenance of elevated blood pressure concurrent with the use of three different anti-hypertensive drugs, one of which is a diuretic. The Renin-Angiotensin-Aldosterone System plays a major role in volume-dependent hypertension. Therefore, its components are interesting targets for genetic association studies. This work focused on the -344 C/T polymorphism in the CYP11b2 gene, which encodes aldosterone synthase. This work evaluates the association between T allele and resistance to anti-hypertensive treatment. Genotyping analysis included 88 subjects with RH, 142 who were responsive to anti-hypertensive treatment and 110 subjects as a control group. Plasmatic concentrations of aldosterone, renin and cortisol, carotid intima-media thickness and carotid-femoral pulse wave velocity were assessed in a smaller subset of hypertensive patients. An association was found between T allele and hypertension (P<0.005), but there was no difference in allele frequencies between both hypertensive groups. There was no difference in plasmatic parameters either, in remodeling indicators between the genotypic groups.